Impact of 3D Rigid Ring Annuloplasty for Tricuspid Regurgitation: A Systematic Review and Meta-Analysis - You, Tao; Ma, Yu-Hu; Yi, Kang; Gao, Jie; Xu, Jian-Guo; Xu, Xiao-Min; He, Shao-E; Wang, Wei; Ji, Meng (Frontiers in Cardiovascular Medicine, 2022)
Abstract Backgrounds: Tricuspid annuloplasty (TAP) is accepted as the standard technique for correcting tricuspid regurgitation (TR). We conducted this present study to provide an overview of the contemporary results of 3D rigid ring annuloplasty for TR. Methods: A systematic literature search was carried out on eight databases to collect all relevant studies on Three-dimensional (3D) rigid ring annuloplasty treatment of tricuspid regurgitation before October 1, 2020. The main outcomes of interest were postoperative TR grade, perioperative mortality and recurrent TR. Results: A total of eight studies were included, all of which were retrospective observational studies. 3D rigid rings were compared with flexible bands, there was no difference in perioperative mortality (OR=1.02; 95％CI [0.52,2.02]; p=0.95), late mortality (OR=0.99; 95％CI [0.28,3.50]; p=0.98), and recurrent TR (OR=0.59; 95％CI [0.29,1.21]; p=0.15). The postoperative TR grade of 3D rigid ring was 0.12 lower (MD=-0.12; 95%CI [-0.22, -0.01]; p=0.03), which manifested that 3D rigid rings have a better postoperative outcome than flexible bands. Compared with suture annuloplasty, the postoperative TR grade of the 3D rigid ring was 0.51 lower (MD=-0.51; 95% CI [-0.59,-0.43]; p<0.05). Within five years follow-up, patients underwent 3D rigid ring annuloplasty also had a lower TR recurrence (OR=0.26; 95% CI [0.13, 0.50]; p<0.05). Conclusions: Compared with suture annuloplasty, 3D rigid rings have early advantages. The 3D rigid rings provided an acceptable short-term effect similar to that of the flexible bands, and the significant difference between them has not been discovered. However, the conclusion was based on limited, short-term data then available. Further research is clearly needed on the long-term effects of 3D rigid ring annuloplasty for TR.